A Novel Tolerogenic Antibody Targeting Disulfide-Modified Autoantigen Effectively Prevents Type 1 Diabetes in NOD Mice - Li, Wei; Zhang, Yan; Li, Ronghui; Wang, Yang; Chen, Lan; Dai, Shaodong (Frontiers in Immunology, 2022)
Increasing evidence suggested that islet amyloid polypeptide (IAPP) is an essential autoantigen in the pathogenesis of type 1 diabetes (T1D) in humans and non-obese diabetic (NOD) mice. A unique disulfide containing IAPP derived peptide KS20 is one of the highly diabetogenic peptides in NOD mice. The KS20-reactive T cells, including prototypic pathogenic BDC-5.2.9, accumulate in the pancreas of prediabetic and diabetic mice and contribute to disease development. We generated a monoclonal antibody (LD96.24) specific to IAg7 (MHCII) -KS20 complexes with high affinity. LD96.24 recognized the KS20 disulfide bond and blocked the interaction between IAg7-KS20 tetramers and cognate T cells, but not other autoantigen reactive T cells. Surprisingly, the in vivo LD96.24 treatment, at either early or late stages, induced tolerance and drastically delayed the onset of T1D disease in NOD mice by reducing the infiltration of not only IAPP specific T cells but also chromogranin A and insulin specific T cells in the pancreas, together with B cells, and dendritic cells. LD96.24 also significantly increased the ratio of Foxp3+ regulatory T cells with IFN-γ secreting effector T cells. The results suggested the important role of disulfide-modified antigens and the thiol redox balance in the development of T1D. Targeting the complexes of MHC/disulfide modified antigens could be a novel immunotherapy for type 1 diabetes.